Government of Tripura Draft Annual Plan 2005-2006 (Write-Up) Planning (P&C) Department - Planning Commission (Planning Commission, 2005)
07. Apart from 8% growth target, the plan envisages creation of 50 million jobs, reducing poverty by 5% and garnering Rs. 80000 cr. through disinvestments and reduction in subsidies in food, fertilizer, and petroleum. It is also emphasized to undertake thorough reforms and remove bottlenecks in Energy, transport and other infrastructure. In the Tenth Plan document State wise target for growth rates has also been prescribed for achieving the national growth rate target. Instead of achieving mere arithmetical economic growth or par capita income, the larger objective of the plan is to improve level of consumption of food and other consumer goods, better access to basic social services e.g. education, health, drinking water, sanitation, expansion of economic and social opportunities and greater participation of the people in the decision making . process.
Write-Up
Government of Tripura